Antimicrobial Peptides and Bacteriophages as Next-Generation Alternatives to Conventional Antibiotics - Sudipta Roy (International Journal of Antibiotics, 2024)
The growing threat of antibiotic-resistant bacteria has underscored the urgent need for innovative alternatives to conventional antibiotics. Antimicrobial peptides (AMPs) and bacteriophages are gaining recognition as next-generation therapeutics due to their distinct mechanisms of action and ability to target resistant pathogens effectively. AMPs, which can be natural or synthetic, disrupt microbial membranes and offer broad-spectrum antimicrobial activity with a reduced likelihood of resistance development. Bacteriophages, as bacteria-specific viruses, provide precise targeting of pathogens while preserving beneficial microbiota and possess the ability to co-evolve with bacterial resistance mechanisms. These approaches hold significant promise for treating challenging infections, including those involving biofilms and multidrug-resistant bacteria. Furthermore, phage therapy can complement traditional antibiotics, potentially reducing the overuse of antibiotics and mitigating the rise of resistance. Additionally, phage cocktails, which combine multiple bacteriophages, enhance the effectiveness and reduce the likelihood of bacterial resistance development, offering a versatile and adaptive therapeutic strategy. However, obstacles, such as ensuring stability, efficient delivery, and navigating regulatory requirements persist. Advances in formulation technologies, including encapsulation and nanotechnology, are paving the way for improved efficacy and clinical implementation. This abstract highlights AMPs and bacteriophages as innovative and sustainable strategies to combat the escalating crisis of antibiotic resistance.
Keywords: Antimicrobial peptides; Bacteriophages; Biofilms; Novel Formulations for Antimicrobial Peptides; antimicrobial resistance